2019
DOI: 10.1002/jia2.25399
|View full text |Cite
|
Sign up to set email alerts
|

Lack of health insurance is associated with delays in PrEP initiation among young black men who have sex with men in Atlanta, US: a longitudinal cohort study

Abstract: Introduction Delays between receiving a PrEP prescription and taking a first dose increase the risk of HIV infection. This is especially relevant in populations with high HIV incidence, such as young black men who have sex with men (YBMSM) in the United States. Additionally, YBMSM have relatively low levels of health insurance. We investigated whether lack of health insurance and reliance on PrEP funding through the manufacturer assistance programme (MAP) leads to delays in initiation of PrEP. Methods HIV‐nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…One research group in the South has demonstrated a delay in PrEP initiation for people who relied on drug manufacturer assistance programs, which require application paperwork similar to insurance companies' prior authorizations. 46 Although some states have laws stating that an insurance company must respond to a medication prior authorization request within 2 days, some states give insurers up to 10 days, and many states have no regulation on response time. 47 If this period only includes business days, it could result in additional delays because of weekends and holidays.…”
Section: Discussionmentioning
confidence: 99%
“…One research group in the South has demonstrated a delay in PrEP initiation for people who relied on drug manufacturer assistance programs, which require application paperwork similar to insurance companies' prior authorizations. 46 Although some states have laws stating that an insurance company must respond to a medication prior authorization request within 2 days, some states give insurers up to 10 days, and many states have no regulation on response time. 47 If this period only includes business days, it could result in additional delays because of weekends and holidays.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these studies examined PrEP initiation based on depressive symptoms and found no relationship. In a longitudinal analysis of 154 Black MSM in Atlanta, GA, depression was not associated with a delay between receiving a PrEP prescription and initiating PrEP [ 53 ]. Similarly, in a prospective observational cohort study with 298 non-Hispanic Black cisgender MSM in Atlanta, GA, depressive symptoms were not associated with PrEP uptake as defined by the date of taking the first PrEP dose after prescription [ 54 ].…”
Section: Depressionmentioning
confidence: 99%
“…The U.S. Public Health Service 2017 guidelines recommend that persons starting PrEP should initiate the medication within 7 days of a negative HIV test (1). However, barriers to obtaining PrEP, such as lack of insurance coverage, can delay initiation and might also adversely affect adherence and persistence for those who have started PrEP (69). Providers and clinical support staff can help adolescents prescribed PrEP by screening for barriers and providing pertinent guidance and support.…”
Section: Medication Initiation Adherence and Persistencementioning
confidence: 99%